A numerical and experimental study on positive diffusive ionization waves in different N2/O2 mixtures: the role of photoionization. (14th February 2023) - Guo, Yulin; Li, Yanru; Zhu, Yifei; Sun, Anbang
Abstract: A diffusive ionization wave can be generated by an ultrafast high voltage far exceeding the inception threshold, and is featured by its unique and repetitive conical morphology. A combinative experimental and numerical study of the diffusive ionization waves is conducted in this work to investigate the role of photoionization in different N2 /O2 mixtures with oxygen concentrations of 20%, 2%, 0.2%, 1 ppm, and pure nitrogen. In all gas mixtures, the ionization wave first forms a spherical shape after its inception then a conical when it approaches the plane electrode. Compared with typical filamentary streamers and inception cloud generated by low overvoltage, photoionization in a diffusive ionization wave takes effects mainly before the formation of the spherical ionization wave, and affects slightly the propagation velocity, discharge morphology, and the width (diameter) of the ionization wave. When the pin-to-plane electrode gap distance is kept 16 mm, in the atmospheric pressure simulation with an 85 kV voltage pulse, the maximum ionization width decreases from 11.4 mm in the 20% mixture to 9.1 mm in pure nitrogen. In the 200 mbar pressure experiment with a 16 kV voltage pulse, the maximum ionization width decreases from 12.5 mm in the 20% mixture to 11.6 mm in pure nitrogen. E in the inception cloud diameter estimation function ( D = 2 U E −1 ) is modified to estimate the width of the ionization wave during its spherical propagation stage. It is shown that the estimation results at 180–205 kV cm −1 are in good agreement with the simulation results at atmospheric pressure air.